Constructing and Experiencing Jewish Identity - Blumenthal, Rachel; Herskowitz, Daniel M.; Mayerhofer, Kerstin (Brill, 2022)
Classification is an inherent feature of all societies. The distinction between Jews and non-Jews has been a major theme of Western society for over two millennia. In the middle of the twentieth century, dire consequences were associated with being Jew ish. Even after the Shoah, the labelling of Jews as "other" continued. In this book, leading historians including Michael Brenner, Elisheva Carlebach and Michael Miller illuminate the meaning of Jewishness from pre-modern and early-modern times to the present day. Their studies offer new perspectives on constructing and experiencing Jewish identity.